2019
DOI: 10.11648/j.jfa.20190703.14
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Audit Committee Characteristics on Modified Audit Opinion in Jordan

Abstract: The Jordanian Corporate Governance Code (JCGC) was first enacted in 2004 and revised in 2017. It offers standards for ethical and decent practices in the corporates. Law in Jordan in 2009 has enforced the formation of an audit committee for all listed companies. Literature has substantiated that the audit committee characteristic (ACCs) impact the quality of financial reporting. This work investigates the role of ACCs in lessening the prospect of corporates in obtaining modified audit opinion in the context of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 60 publications
(179 reference statements)
0
12
0
Order By: Relevance
“…Regarding the relation between AC characteristics and auditing measures, Kikhia (2014) found that AC independence was positively associated with audit fee levels, though he found no statistically significant association between audit fee levels and AC meetings nor AC member expertise. Finally, Alkilani et al. (2019) found that AC member expertise is likely to lead to less modified audit opinions, unlike AC size, AC independence or AC number of meetings, where that relation was not found.…”
Section: Background Of the Studymentioning
confidence: 93%
“…Regarding the relation between AC characteristics and auditing measures, Kikhia (2014) found that AC independence was positively associated with audit fee levels, though he found no statistically significant association between audit fee levels and AC meetings nor AC member expertise. Finally, Alkilani et al. (2019) found that AC member expertise is likely to lead to less modified audit opinions, unlike AC size, AC independence or AC number of meetings, where that relation was not found.…”
Section: Background Of the Studymentioning
confidence: 93%
“…The vital role and responsibility of audit committees in the financial and monitoring process are demonstrated in the recent literature (Alqatamin, 2018;Alzoubi, 2019;Al-Hajaya, 2019;Nazari, and Soukhakyan, 2020). These studies recommend that audit committee performance promote and develop the FRQ by way of enhancing audit quality, internal monitoring systems and communication with external auditors (Alkilani and Hussin, 2019;Shatnawi, and Eldaia, 2019).…”
Section: The Performance Of the Audit Committeementioning
confidence: 99%
“…To minimize the effect of the expunged variables and to increase the predictive ability of the model we include several control variables (Farinha & Viana, 2009;Firth, et al, 2007). Variables such as audit firm size, audit report lag, losses and operating cash flow; prior studies have uncovered an association with modified audit opinion (Pucheta-Martínez & de Fuentes, 2007;Firth, et al, 2007;Goh, 2009;Farinha & Viana, 2009;Rahmat, Iskandar, & Saleh, 2009;Sultanoglu, Mugan, Sekerdag, & Oran, 2018;Alkilani, Hussin, & Salim, 2019a). Table 2 presents the descriptive statistics and univariate test results for (dummy) variables by audit opinion.…”
Section: Methodsmentioning
confidence: 99%